Spatial heterogeneity analyses of pore structure and mineral composition of Barnett Shale using X-ray scattering techniques. (December 2021) - Wang, Qiming; Hu, Qinhong; Ning, Xuewei; Ilavsky, Jan; Kuzmenko, Ivan; Tom, Tristan
Abstract: The spatial heterogeneity of pore structure and mineral composition at μm to mm scales in mm to cm-sized shale samples complicates the laboratory measurements of porosity & pore size distribution and consequently reservoir quality evaluation. Traditional fluid invasion characterization methods typically take hours to days to get data and can only test relatively small samples (usually 2.54 cm diameter core plugs and mm-sized rock chips). The X-ray scattering techniques at the Advanced Photon Source of the Argonne National Laboratory have the capability to non-destructively determine the pore structure and mineral composition of mm × mm area in a short time of seconds and to hold several to hundreds of mm 2 sized sample to conduct large area heterogeneity analysis in the short duration of hours. With the use of ultra-small angle X-ray scattering (USAXS), small-angle X-ray scattering (SAXS), and wide-angle X-ray scattering (WAXS), the porosity, surface area and pore size distribution of two Barnett Shale samples have been mapped out and the mineral compositions are determined qualitatively. Overall, the porosity and pore surface area of the Barnett Shale Sample A over a 36 cm 2 area ranges from 1.70 % to 8.13 % and 8.87 m 2 /g to 40.2 m 2 /g respectively. The porosity and surface area of Sample B over a 24 cm 2 area varies from 3.15 % to 11.7 % and 18.3 m 2 /g to 60.2 m 2 /g. In Sample A, the mineral composition shows a shift from carbonate-rich to siliciclastic-rich over a distance of several millimeters. For Sample B, the mineral compositions are mainly siliciclastic and do not show an obvious lithological change. The direct observations of high spatial heterogeneity of pore structure and mineral composition in shale illustrate the utility of integrated X-ray scattering techniques to provide valuable insights into shale studies and reservoir evaluation. Highlights: We used ultra-small angle X-ray scattering (USAXS), small-angle X-ray scattering (SAXS), and wide-angle X-ray scattering (WAXS) in an integrated fashion. Porosity, surface area and pore size distribution of two Barnett Shale samples were mapped out and the mineral compositions qualitatively determined. Results showed direct observations of high spatial heterogeneity of pore structure and mineral composition in shale, which is related to its lithological difference.